PENERAPAN METODE PREFERENCE SELECTION INDEX (PSI) UNTUK MENENTUKAN PRIORITAS PENANGANAN FAKTOR PENGHAMBAT PRODUKSI SERAT ABAKA - Cristo Mailantang; Agung Sutrisno; Jefferson Mende (JURNAL POROS TEKNIK MESIN UNSRAT, 2022)
The production process is one of the important activities of the company that needs to be considered considering its key role in the operation or absence of a business. Related to this importance, this study aims to determine the various types of inhibiting factors in the Abaka Fiber (Musa textilis Nee) production process and create a ranking model by applying the Preference Selection Index (PSI) method. The results of the application of the Preference Selection Index (PSI) method in the Abaka Fiber Production case study showed nine types of inhibiting factors. Meanwhile, in terms of ranking of inhibiting factors, the priority of inhibiting factors ranked first is occupied by inhibiting factors. The craftsmen do not know the technology to develop the Abaka fiber processing process with a preference score of 0.47. Keywords: Inhibitory Factors, Preference Selection Index (PSI) Method, Abaka Fiber